Analyzing the Impact of BTS on Resolving the Problem of Youth Mental Health - Sihombing, Lambok Hermanto (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
This Journal outlines the efforts of BTS as a K-pop boy group to help to resolve the problem of Youth Mental Health, in which Korea itself has a background as one of the countries with the most mental health cases in the world. More deeply, in this study, the writer conducted an analysis of several forms of BTS activities that show their efforts in reducing mental health problems, in this case including; song lyrics in the BTS album, the social campaign they run with UNICEF,